A DAB2IP genotype: sex interaction is associated with abdominal aortic aneurysm expansion. (11th July 2017) - Ye, Zi; Austin, Erin; Schaid, Daniel J; Bailey, Kent R; Pellikka, Patricia A; Kullo, Iftikhar J
Abstract : A faster expansion rate of abdominal aortic aneurysm (AAA) increases the risk of rupture. Women are at higher risk of rupture than men, but the mechanisms underlying this increased risk are unknown. We investigated whether genetic variants that influence susceptibility for AAA ( CDKN2A-2B, SORT1, DAB2IP, LRP1 and LDLR ) are associated with AAA expansion and whether these associations differ by sex in 650 patients with AAA (mean age 70±8 years, 17% women) enrolled in the Mayo Clinic Vascular Disease Biorepository. Women had a mean aneurysm expansion 0.41 mm/year greater than men after adjustment for baseline AAA size. In addition to baseline size, mean arterial pressure (MAP), non-diabetic status, SORT1- rs599839[G] and DAB2IP- rs7025486[A] were associated with greater aneurysm expansion (all p<0.05). The associations of MAP and rs599839[G] were similar in both sexes, while the associations of baseline size, pulse pressure (PP) and rs7025486[A] were stronger in women than men (all p - sex interaction ≤0.02). A three-way interaction of PP*sex* rs7025486[A] was noted in a full-factorial analysis (p=0.007) independent of baseline size and MAP. In the high PP group (≥median), women had a mean growth rate 0.68 mm/year greater per [A] of rs7025486 than men (p - sex interaction =0.003), whereas there was no difference in the low PP group (p - sex interaction =0.8). We demonstrate that variants DAB2IP- rs7025486[A] and SORT1- rs599839[G] are associated with AAA expansion. The association of rs7025486[A] is stronger in women than men and amplified by high PP, contributing to sex differences in aneurysm expansion.